2019
DOI: 10.1155/2019/8407206
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Extract Ameliorates Ischemia-Induced Retinal Ganglion Cell Degeneration in Rats

Abstract: Purpose. Oxidative stress induced by reduced blood circulation is a critical pathological damage to retinal ganglion cells (RGCs) in glaucoma. We previously showed that green tea extract (GTE) and its catechin constituents alleviate sodium iodate-induced retinal degeneration in rats. Here, we investigated the therapeutic effect of GTE on ischemia-induced RGC degeneration in rats. Methods. RGC degeneration was induced by ischemic reperfusion in adult Fischer F344 rats. Green tea extract (Theaphenon E) was intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The retinas have very high oxygen consumption and are sensitive to oxygen deficiency [1,2]. Retinal ischemia is related to the atherosclerosis of retinal vessels and carotid arteries, diabetic retinopathy, glaucoma, and endocrine ophthalmopathy [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The retinas have very high oxygen consumption and are sensitive to oxygen deficiency [1,2]. Retinal ischemia is related to the atherosclerosis of retinal vessels and carotid arteries, diabetic retinopathy, glaucoma, and endocrine ophthalmopathy [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic studies, performed in rats, indicated that after oral intake of GTE, catechins (e.g., EGCG, EGC, and EC) are quickly distributed into various eye compartments and exert pro- and antioxidative effects depending on the tissues and EGCG concentration [ 228 ]. Yang et al (2019) demonstrated that an intragastric administration of GTE, 4 times/day with a dose of 275 mg/kg, ameliorated ischemia-induced RGC degeneration and prevented RGC function impairment through antiapoptotic, antioxidant, and anti-inflammatory effects [ 229 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…The antioxidative effect of green tea extract has also been used in a study by Yang et al [35]. They evaluated this antioxidative effect on the retinal ganglion cell loss produced by retinal ischemia-reperfusion induced by raisin intraocular pressure up to 110 mmHg.…”
Section: Astaxanthin (Ast)mentioning
confidence: 99%